FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN INFRASTRUKTUR PERIODE 2018-2021 - Junika, Junika; Jonnardi, Jonnardi (Jurnal Paradigma Akuntansi, 2025)
1)This research aims at how profitability, capital structure, and asset turnover affect firm value and the impact of exchange rate on these relationshop on 2) infrastructure sector companies listed on the Indonesia Stock Exchange during 2018-2021. 3)Sample was selected using simple random sampling method and the valid data was 4)27 companies. 5)Data processing techniques using 6)multiple regression analysis what helped by Eviews (Econometrical Views) 9 and Microsoft Excel 2013. 7) The results of this study indicate that partially profitability has a positive and significant effect on firm value. Meanwhile, total asset turnover has a positive and insignificant effect on firm value, and capital structure has a negative and insignificant effect on firm value. The exchange rate is able to strengthen the effect of profitability on firm value. However, the exchange rate is unable to moderate the effect of capital structure and total asset turnover on firm value.8) The implication of this study is that companies need to improve their profitability performance which will increase the firm value, and that will bring a good signal for investors.